Transcranial Direct Current Stimulation Reduces Craving in Substance Use Disorders: A Double-blind, Placebo-Controlled Study. Issue 3 (September 2019) - Martinotti, Giovanni; Lupi, Matteo; Montemitro, Chiara; Miuli, Andrea; Di Natale, Chiara; Spano, Maria Chiara; Mancini, Valerio; Lorusso, Marco; Stigliano, Gianfranco; Tambelli, Antonio; Di Carlo, Francesco; Di Caprio, Lucia; et al.
Abstract : Objectives: The use of transcranial direct current stimulation (tDCS) in addiction disorders is still on its rise in comparison with pharmacological and psychotherapeutic strategies that still show low level of evidence. In this study, we aimed to evaluate the efficacy of the anodic tDCS for the short-term treatment of substance craving and other psychiatric symptoms. Methods: In this randomized, double-blind, sham-controlled trial, inclusion criteria included the diagnosis of substance use disorder and/or gambling disorder. The protocol includes 5 consecutive days of active or sham tDCS session. Cathode was placed over the left dorsolateral prefrontal cortex. Hamilton Depression Rating Scale, Hamilton Anxiety Rating Scale, Young Mania Rating Scale, Barratt Impulsiveness Scale, South Oaks Gambling Screen, and visual analog scale (VAS) 1 to 10 for craving were administered at the baseline (T0) and after 5 days of treatment (T1). Results: Thirty-four treatment-seeking subjects were randomized to sham (n = 16) and active stimulation (n = 18) groups. A statistically significant reduction of values at T1 was found in all subjects considering VAS ( P < 0.001), Hamilton Depression Rating Scale ( P < 0.001), Hamilton Anxiety Rating Scale ( P < 0.001), and Barratt Impulsiveness Scale 11 ( P = 0.032). A significant reduction for VAS craving in favor of the active stimulation ( P = 0.011) was found. Conclusions: Our findings reveal a statistically significant rapid reduction of craving in the active tDCS group on the right dorsolateral prefrontal cortex with respect to sham group, confirming the scientific literature trend. Large samples, with maintenance tDCS therapy and long-term follow-up, are required to establish the potential of this noninvasive and easily delivered brain stimulation strategy.